Network Effects in Migrant Remittances: Evidence From Household, Sibling, and Village Ties in Nang Rong, Thailand. (August 2015) - Garip, Filiz; Eskici, Burak; Snyder, Ben
Migrant remittances comprise an important capital source for developing countries. Research connects migrants' remittance behavior to altruism, exchange, insurance, and investment motives or to a desire to maintain options available through origin communities. This study provides an alternative "network" perspective: Remittance behavior may depend on the remitting patterns of those in one's social ties—(a) to members of the origin household; (b) to members of "sibling" households, where a member of the ego household has a sibling; and (c) to members of the origin village. We use censuses from 51 villages in Nang Rong, where one in four residents migrated to internal destinations in either 1994 or 2000, and about one in two migrants remitted to their origin households. We observe network effects: Migrants' likelihood of remitting increases with the number of remitters in the household and with the share of remitters in the village, net of village and year fixed effects, and other potential confounders. We link the former pattern to inheritance-seeking behavior in the household, and the latter to shared norms in the village.